Hydrogenation and dehydrogenation of dinuclear Boron- and Gallium hydrides: quantum chemical calculations and experiments - Himmel, Hans-Jörg (Modeling of molecular properties, 2011)
This chapter contains sections titled: Dihydrogen Activation with Main-Group Element Compounds Preliminary Quantum Chemical Calculations Experimental Studies in Concert with Quantum Chemical Calculations References
Gesehen am 22.09.2020